Evaluating the bioequivalence of levetiracetam brand and generic oral tablets available in the Saudi market in vivo - Danah ALRabeeah; Aliyah Almomen; Nourah Alzoman; Maria Arafah (Elsevier, 2023)
Background: Epilepsy is a common global neurological disorder. About 30% of epileptic patients are managed with anti-epileptic Drugs (AEDs). Since 2000, Levetiracetam (LEV) has been marketed around the world as an AED under the brand name Keppra, and recently more generics are found in the Saudi market as cheaper alternatives. The objective of this study is to evaluate the bioequivalence of LEV brand and generics available in the Saudi market in mice. Methods: Pharmacokinetics (PK), liver function test, and behavioral studies were conducted for LEV brand and generic in different groups of Blab/c mice. Results: PK results show a significance difference in PK parameters mostly evidenced with generic 3, then generic 2. The only significant different between Keppra and generic 1 was in T1/2. In addition, Keppra did not significantly increase liver enzymes in comparison to other generics. On the other hand, other generics showed less favorable results in increasing liver enzymes. Keppra reduced the number and intensity of epileptic attacks, had no mortality rate due to epilepsy, and was associated with less sever seizures attacks. Conclusion: Keppra, the brand form of LEV, has better safety and efficacy profiles in mice compared to 3 generics found in the Saudi market. Therefore, we recommend evaluating the same parameters tested in this study in patients utilizing similar generics and brand to establish the existence of bioequivalence between LEV brand and generics.